Comparative studies of optical absorption, photoluminescence and EPR spectra of PbMnI₂ bulk layers and nanocrystals - Savchuk, A.I.; Stolyarchuk, I.D.; Savchuk, O.A.; Shporta, O.A.; Stefaniuk, I.; Rogalska, I.; Sheregii, E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
We report a study of the layered diluted magnetic semiconductor (DMS)
Pb₁₋xMnxI₂ in 3D bulk layers and nanocrystal form by using optical absorption,
photoluminescence and electron paramagnetic resonance (EPR). The samples of the bulk
Pb₁₋xMnxI₂ crystals with x lying within the range 0 to 0.15 were grown using the
Bridgman-Stockbarger technique. The composite nanostructures containing DMS
nanocrystals of Pb₁₋xMnxI₂ were prepared by cooling the boiling saturated aqueous
solution to room temperature. The exciton structure of the absorption spectra of
nanoparticles exhibits blue shift due to the quantum confinement effect. In
photoluminescence spectra of nanocrystals, two main peaks were revealed, which are
attributed to the band-edge transitions and defect states. The EPR spectra for bulk layers
and nanocrystals consist of an intense broad line and several weak narrow lines that
correspond to hyperfine spectra of Mn²⁺ ions.